Peningkatan Prestasi Belajar PKn melalui Metode Kooperatif Pada Siswa SD - Christina Suhartini (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2018)
Abstract. The formulation of the problem in this study is whether the cooperative method can be used to improve PKn learning achievement for grade IV students of SD Negeri 2 Nanggulan, District of Cawas, Klaten Regency, second semester 2017/2018 academic year? The goal to be achieved is to prove that the cooperative method can be used to improve PKn learning achievement of grade IV students of SD Negeri 2 Nanggulan, District of Cawas, Klaten Regency, second semester of the school year 2017/2018. This research was conducted at Nanggulan Cawas Klaten Public Elementary School 2. While the time of the study wasconducted from February to March 2018. The subjects of this study were grade IV students of SD Negeri 2 Nanggulan Cawas Klaten in the second semester of the school year 2017/2018. This action research uses the classroom action research flow. The data analysis technique used uses several stages, namely data reduction, presentation and conclusion. From the results of the research carried out since planning, repairs to implementation and evaluation, it can be concluded that the cooperative method can be used to improve PKn learning achievement of fourth grade students of SDN 2 Nanggulan, District of Cawas, Klaten Regency, second semester 2017/2018 school year. This was proven before the improvement in the percentage of students' completeness in learning was only 27.78% or 5 students, in the improvement of the first cycle to 55.6% (of 18 students, which was not completed 8 students) and in the second cycle the percentage of student mastery reached 94, 44%. Of the 18 students, 17 of them have achieved mastery learning, while the one student is still incomplete.